2021
DOI: 10.1016/j.omtn.2021.01.019
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hypoxic tumor-derived exosomal circular RNA SETDB1 promotes invasive growth and EMT via the miR-7/Sp1 axis in lung adenocarcinoma

Abstract: Hypoxia is a common feature of solid tumors and has been associated with tumor aggressiveness and poor prognosis. Exosomes are involved in mediating cellular-environment interactions. Circular RNAs (circRNAs) are a class of non-coding RNA broadly found in cells and exosomes. However, the functions and regulatory mechanisms of exosomal circRNAs induced by hypoxia remain poorly understood in lung adenocarcinoma (LUAD) development. Differentially expressed circRNAs were identified between exosomes extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…Bioinformatics analysis of exosomal circRNA microarray data to explore the ceRNA regulation network revealed that ceRNA essentially operates in an miRNA-target mechanism [ 36 ]. The number of MREs is the key determinant of the range and strength of ceRNA regulation [ 37 , 38 ]. Several validated ceRNA networks participate in the initiation and progression of various diseases [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis of exosomal circRNA microarray data to explore the ceRNA regulation network revealed that ceRNA essentially operates in an miRNA-target mechanism [ 36 ]. The number of MREs is the key determinant of the range and strength of ceRNA regulation [ 37 , 38 ]. Several validated ceRNA networks participate in the initiation and progression of various diseases [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RT-qPCR analysis showed that the concentrations of those increased miRNAs were 1000-fold above the cellular level, which may better distinguish acute myeloid leukemia from healthy volunteers with high sensitivity and specificity ( Hornick et al, 2015 ). High levels of circular RNA SETDB1 and miR-31-5P are observed in lung adenocarcinoma patients ( Xu et al, 2021 ; Yu et al, 2021 ). Serum vesicular circular RNA SETDB1 level is closely correlated with the T stage and lymph node metastasis ( Xu et al, 2021 ).…”
Section: Tumor-derived Evs As Biomarkers In Cancer Diagnosis and Treatmentmentioning
confidence: 99%
“…High levels of circular RNA SETDB1 and miR-31-5P are observed in lung adenocarcinoma patients ( Xu et al, 2021 ; Yu et al, 2021 ). Serum vesicular circular RNA SETDB1 level is closely correlated with the T stage and lymph node metastasis ( Xu et al, 2021 ). In addition, zinc finger antisense 1 (ZFAS1), belonging to competing endogenous lncRNA, is enriched in the serum EVs of gastric cancer patients ( Pan et al, 2017 ).…”
Section: Tumor-derived Evs As Biomarkers In Cancer Diagnosis and Treatmentmentioning
confidence: 99%
“…In Non-Small Cell Lung Cancers (NSCLC), upregulated SETDB1 expression favors tumor progression through interaction and methylation of p53 and Akt (AKT Serine/Threonine Kinase 1) [ 68 , 69 , 70 ], resulting in poorer prognosis and tumor recurrence in patients with stage I NSCLC [ 71 , 72 ]. According to a recent study, SETDB1-derived circular RNA (circSETDB1) was significantly increased in lung adenocarcinoma hypoxia-induced exosomes and was associated with disease stage, whereas circSETDB1 knockdown notably inhibited in vitro malignant growth [ 73 ]. SETDB1 also activates the Wingless-related integration site (WNT) pathway, causing the accumulation of nuclear β-catenin and induction of a cancerous phenotype [ 74 ].…”
Section: Connection Of Setdb1 With Tumorigenesismentioning
confidence: 99%